Frequency of Junk Food and Depression in Children - Uroosa asif qureshi, Muhammad waqaruddin sheroze, Narmeen shahid, Nazish iqbal; Mehwish zehra, Zainab hayat khan, Tooba afzal; Muhammad Ayoob Memon, Ruba Ali Zahid; Wahab, Amna; Kalar, Musleh Uddin; Vincent, Mathew (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Consumption of junk food has a profound detrimental effect on psychological health. Participants who ate commercial foods especially doughnuts were at risk of mental health problems. Materials and Methods: This cross sectional study was conducted at private colleges and the participants were college students whom were selected on the basis of non-probability convenient sampling. The sample size calculation was done using the W.H.O. software. Participants who had completed questionnaire were included and were excluded if they were on antidepressant medication. Questionnaire for this study was the New Zealand Adolescent Frequency Food Questionnaire. Results: majority of the students eat fast food on monthly basis 134(47.3%), while 94(33.2%) eat fast food on weekly basis, 39(13.8%) of the students eat fast food twice weekly and 15(5.3%) on daily basis. Factor analysis showed 24% correlation matrix of eating fast food with drinking fruit juice, 30% correlation with drinking tea or coffee, 37% correlation with milky drinks and 35% correlation with consumption of sugary drinks. The variable of how often you eat sweets showed 33% correlation with you were not able to feel happy, 32% you felt scared, 31% correlation with your sleep was restless and 32% correlation with you felt that people disliked you. One way ANOVA revealed statistically significant results and the Tukey pos hoc test showed that comparison of students from age 20- 25 years eating junk food with depression scores was also statistically significant. Conclusion: This research shows a positive correlation between consumption of junk food and occurrence of depression in children.